REVITALIZATION OF BEACH TOURISM AREA THROUGH INTEGRATED WASTE CLEANUP MOVEMENT FOR ENVIRONMENTAL SUSTAINABILITY, CASE STUDY: TIRANG ISLAND - Muhammad Yusuf Pratama; Luthfan Nursyamsul Ahfi; Alfin Isy Ni’mah; Naqiyatuz Zakia; Muhammad Nabil Amjad; Khusnul Mariah; Hardiansyah Tri Bima; Mutma’inah Mutma’inah (Biro Administrasi dan Akademik, 2025)
Humans are consumers who depend on natural products and the environment, but human awareness in maintaining and preserving nature is still very low. This research is a form of service and uses a participatory approach that involves elements of the community and the management of tourist attractions. The activity was carried out by observation and then continued with 3 stages of activity, namely program socialization, beach clean-up action and waste management system education. This research is aimed at educating the community in protecting the environment and pouring it into a real movement. This research contributed significantly in revitalizing the condition of Tirang beach from full of garbage to clean again with a sustainable waste management system run by the local community.